2021
DOI: 10.1109/joe.2021.3062047
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Sizing and Optimizing the Energy System on Long-Range AUVs

Abstract: Autonomous underwater vehicles (AUVs) are utilized in a variety of unmanned missions, such as environmental surveys or guarding coastal waters. Currently, the most commonly used energy storage is a secondary battery pack. A potential solution for increasing the range even further on larger AUVs is to utilize hybrid fuel cell/battery systems. Fuel cell systems can have a significantly increased specific energy compared to batteries and are now starting to become well-developed technologies. However, in an under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…For each mission considered, the same procedure as used for the 50 h mission is implemented, and the score of each alternative is calculated using both the entropy and the CRITIC weighting methods, see Figures 4 and 5. For both methods, and for all alternatives, the score changes when increasing the length of mission from 1 to 100 h, while a plateau is reached when duration of mission exceeds 100 h. This trend is due to the fact that the energy density and specific energy of the hybrid systems reach an asymptote when the mission duration increases, as observed in [4]. Furthermore, the best-ranked alternatives remain the same (A 8 , A 7 and A 2 ) for both methods when the mission becomes longer than 20 h, while the worst-ranked alternative is always the combination of Comp H 2 and H 2 O 2 (A 3 ).…”
Section: Influence Of the Mission Durationmentioning
confidence: 69%
See 3 more Smart Citations
“…For each mission considered, the same procedure as used for the 50 h mission is implemented, and the score of each alternative is calculated using both the entropy and the CRITIC weighting methods, see Figures 4 and 5. For both methods, and for all alternatives, the score changes when increasing the length of mission from 1 to 100 h, while a plateau is reached when duration of mission exceeds 100 h. This trend is due to the fact that the energy density and specific energy of the hybrid systems reach an asymptote when the mission duration increases, as observed in [4]. Furthermore, the best-ranked alternatives remain the same (A 8 , A 7 and A 2 ) for both methods when the mission becomes longer than 20 h, while the worst-ranked alternative is always the combination of Comp H 2 and H 2 O 2 (A 3 ).…”
Section: Influence Of the Mission Durationmentioning
confidence: 69%
“…The use of a hydrogen fuel cell can increase significantly the energy content in the AUV, and therefore its endurance [1][2][3]. It was demonstrated that for missions longer than a few hours, volume-optimized hybrid fuel cell/battery systems are more relevant for AUVs than full battery systems, as they combine the high energy density of fuel cells and the power flexibility of batteries [4]. Since the late 90s, several projects have demonstrated the capabilities of low temperature fuel cell-powered AUVs using various hydrogen and oxygen storage units, fuel cells and batteries [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the improvement of people's understanding of the ocean, the exploration and development of Marine environments covering 70% of the surface has received extensive attention. Autonomous underwater observation vehicle is an autonomous underwater equipment suitable for various environments, characterized by long working hours and wide range of activities [ 1 6 ]. Therefore, the energy supply requirements of this equipment are relatively high.…”
Section: Introductionmentioning
confidence: 99%